Transporte de ovos e comportamento larval de Prochilodus lineatus (VALENCIENNES, 1836) em canal simulador de deriva - Queiroz, Thays Cristine Bellenzier de (2019)
The objective of this study was to evaluate the egg drift and the behavior of corimba larvae (Prochilodus lineatus VALENCIENNES, 1836) against different flow velocities in a drift simulator channel (DSC). For the experiment, the flow velocities were determined, being: 0.032 m/s, 0.044 m/s, 0.068 m/s and 0.081 m/s. The eggs and larvae used in the experiment were obtained from induced spawning and stored in a 200 liter conical-cylindrical fiberglass incubator with constant water circulation, at an average temperature of 21.6ºC. The eggs passed through the canal every 4 hours and the larvae every 8 hours from hatching until they reached 16 hours of development. Tests were then performed at 12-hour intervals. In the samples, 10 individuals (replicates) were used for each of the 4 flow velocities tested, where the speed and the transport distance and the swimming behavior of the larvae were observed. The transport of P. lineatus eggs during the experiment was proportional to the increase of the flow, being mostly near the surface. Soon after hatching, the larvae have already tried to position themselves against the flow within the canal, indicating that even the poorly developed ones have position and orientation perception. Larger transport velocities occurred during early developmental periods, being completely transported or following the direction of flow (negative reotaxis). Thus, based on the data obtained in this study, we can conclude that environments whose flow velocity is less than 0.044 m/s are not favorable for P. lineatus egg drift, while velocities above 0.081 m/s provide higher probabilities of successfully transporting eggs to downstream areas. We can also conclude that the larvae showed active behavior from the first hours of development with behavior similar to that presented in a natural environment and that after 48 hours after hatching they are able to maintain and disperse against the flow within the channel.